Meat Hook Injury Leading to Brain Abscess: A Rare Occurrence - Diyora, Batuk; Dhall, Gagan; Patel, Mehool; Mulla, Mazharkhan; More, Nilesh; Shah, Amit (Indian Journal of Neurotrauma, 2021)
Transorbital orbitofrontal penetrating injury by a nonmissile object is uncommon. The presentation of this injury varies. This injury can be easily missed during the initial clinical presentation, because the foreign body is sometimes not visible on local examination, the wound on the orbital skin is small, and very subtle signs are present. The patient can present with delayed complications of the primary injury. Our patient was a 33-year-old male who presented with an orbitofrontal injury with a meat hook. He had minor symptoms at the time of presentation, which were overlooked. Three weeks later, he developed signs and symptoms of raised intracranial pressure (ICP). Brain imaging revealed a peripheral rim of contrast-enhancing mass lesion in the right frontal lobe, extending into the right orbit with perilesional edema suggestive of posttraumatic brain abscess. Via right frontal craniotomy, pus was drained out and abscess wall was excised. The patient made good clinical recovery. A higher index of suspicion and sound knowledge of occult penetrating injury patterns is required in the cases of orbital injuries. Appropriate radiological imaging can lead to an earlier and accurate diagnosis, and can prevent its delayed sequela like brain abscess.
Keywords: intracerebral abscess; transorbital injury; intracranial penetrating injury; meat hook; occult transorbital injury